RELIGIOUS MODERATION IN ISLAMIC EDUCATION LEARNING: COMPARATIVE INSIGHTS FROM TWO PESANTREN-ORIENTED SCHOOLS - Rahman, Abdul; Djubaedi, Dedi; Sahrodi, Jamali; Duryat, Masduki; Kholifah, Afiyatun (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
This study is motivated by the importance of strengthening religious moderation values through pesantren-based Islamic Religious Education (PAI) in addressing moral and social challenges within educational environments. Pesantren-based schools have the potential to instill the values of tawassuth (moderation), tasamuh (tolerance), tawazun (balance), and i’tidal (justice) through instructional processes and institutional culture. However, differences in the level of pesantren integration within educational institutions influence how these values are internalized. This study aims to analyze differences in the planning, implementation, and evaluation of religious moderation value internalization at SMK Mekanika Buntet Pesantren and SMA IT Akmala Sabila in Cirebon Regency, as well as to identify supporting and inhibiting factors. This research employs a qualitative phenomenological approach involving school principals, Islamic Religious Education teachers, and students as participants. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion verification. The findings indicate that pesantren system integration supports a more structured internalization of moderation values through religious habituation, teacher role modeling, and institutional culture. This study highlights the importance of integrating pesantren values into Islamic Religious Education to support the development of moderate and ethical student character.